Repetitive Mild Traumatic Brain Injury in Rats Impairs Cognition, Enhances Prefrontal Cortex Neuronal Activity, and Reduces Pre-synaptic Mitochondrial Function - Feng, Yin; Li, Keguo; Roth, Elizabeth; Chao, Dongman; Mecca, Christina M.; Hogan, Quinn H.; Pawela, Christopher; Kwok, Wai-Meng; Camara, Amadou K. S.; Pan, Bin (Frontiers in Cellular Neuroscience, 2021)
A major hurdle preventing effective interventions for patients with mild traumatic brain injury (mTBI) is the lack of known mechanisms for the long-term cognitive impairment that follows mTBI. The closed head impact model of repeated engineered rotational acceleration (rCHIMERA), a non-surgical animal model of repeated mTBI (rmTBI), mimics key features of rmTBI in humans. Using the rCHIMERA in rats, this study was designed to characterize rmTBI-induced behavioral disruption, underlying electrophysiological changes in the medial prefrontal cortex (mPFC), and associated mitochondrial dysfunction. Rats received 6 closed-head impacts over 2 days at 2 Joules of energy. Behavioral testing included automated analysis of behavior in open field and home-cage environments, rotarod test for motor skills, novel object recognition, and fear conditioning. Following rmTBI, rats spent less time grooming and less time in the center of the open field arena. Rats in their home cage had reduced inactivity time 1 week after mTBI and increased exploration time 1 month after injury. Impaired associative fear learning and memory in fear conditioning test, and reduced short-term memory in novel object recognition test were found 4 weeks after rmTBI. Single-unit in vivo recordings showed increased neuronal activity in the mPFC after rmTBI, partially attributable to neuronal disinhibition from reduced inhibitory synaptic transmission, possibly secondary to impaired mitochondrial function. These findings help validate this rat rmTBI model as replicating clinical features, and point to impaired mitochondrial functions after injury as causing imbalanced synaptic transmission and consequent impaired long-term cognitive dysfunction.